1999
DOI: 10.1172/jci7936
|View full text |Cite
|
Sign up to set email alerts
|

Naturally processed and presented epitopes of the islet cell autoantigen IA-2 eluted from HLA-DR4

Abstract: During immune responses, antigen-presenting cells (APCs) process antigens and present peptide epitopes complexed with human leukocyte antigen (HLA) molecules. CD4 cells recognize these naturally processed and presented epitopes (NPPEs) bound to HLA class II molecules. Epitope identification is important for developing diagnostic and therapeutic tools for immune-mediated diseases and providing insight into their etiology, but current approaches overlook effects of natural processing on epitope selection. We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(136 citation statements)
references
References 54 publications
4
131
0
1
Order By: Relevance
“…Peptide panel The peptide panel was derived from that used by Arif et al [25] and included IA-2 and proinsulin peptides naturally processed and presented by HLA-DR4 (previously identified by Peakman et al [32] and Arif et al [25], respectively), as well as three 'promiscuous epitopes' from tetanus toxoid used as controls for the specificity of the T cell response [25,33]. Table 1 summarises the peptides used and their sequences.…”
Section: Methodsmentioning
confidence: 99%
“…Peptide panel The peptide panel was derived from that used by Arif et al [25] and included IA-2 and proinsulin peptides naturally processed and presented by HLA-DR4 (previously identified by Peakman et al [32] and Arif et al [25], respectively), as well as three 'promiscuous epitopes' from tetanus toxoid used as controls for the specificity of the T cell response [25,33]. Table 1 summarises the peptides used and their sequences.…”
Section: Methodsmentioning
confidence: 99%
“…While the decreasing proinsulin-specific responses and the increasing of IGRP [265][266][267][268][269][270][271][272][273] reactivity are reminiscent of NOD mouse data (6), the finding of a similar phenomenon for GAD and IA-2 is unparalleled. This is not surprising, since GAD and IA-2 are thought to be important target Ags in human type 1 diabetes (15,17,26,(37)(38)(39) but not in the NOD mouse (40 -43). Consideration of additional epitopes poorly recognized at type 1 diabetes onset (17,18) may reveal further specificities becoming immunodominant at later time points.…”
Section: Cd8mentioning
confidence: 99%
“…Another study identified naturally processed and presented epitopes of the intracellular domain of the Type 1 diabetes-associated autoantigen IA-2, presented by HLA-DR4 (DRB1*0401) [65]. IA-2ic-derived peptides were eluted from HLA-DR4 that constituted six sets of peptides nested around distinct core regions.…”
Section: Genetic and Environmental Factors Associated With T-cell Autmentioning
confidence: 99%